Notes on the Gini Coefficient - Sethi, Rajiv (Journal of Income Distribution®, 2024)
This note examines two measures of inequality, both of which can be traced back to Corrado Gini, and both of which have been axiomatized. One is the standard Gini coefficient, which is a completion of the partial order obtained by piecewise linear interpolation of the points that form the basis of the Lorenz curve (the Lorenz points). It is argued that the other measure, which might also be called a Gini coefficient, is inconsistent with the partial order obtained by any interpolation of the Lorenz points.